Analisis Minat Belajar Siswa Kelas III Pada Materi Bangun Datar Berbantuan VBA - Dzarroh Qolba Musoffa; Ani Nurhayati; Siti Chotimah (Journal on Education, 2020)
Interest in learning is one of the soft skills that are important for students to have. Because interest in learning will make it easier for students to achieve learning goals. While a lack of interest in learning can result in a lack of interest in a person in a particular field, it can even lead to rejection of the teacher. The focus of our research on the research sample is to determine the criteria for student interest in learning. This research is motivated by most elementary school (SD) students who do not like learning mathematics because mathematics is a subject that deals with numbers. This shows that students are less interested in learning mathematics. The method used in this research is descriptive qualitative with a sample of 11 people. The results of this study indicate the criteria for student interest in learning with the help of VBA are in the high category because the average percentage accumulation is 85.34%. The VBA application is a learning medium that is arguably something new for elementary students in general. So that when the media is used in learning, it can attract students to pay attention and follow learning well.